Evidence of muscarinic acetylcholine receptors in the retinal centrifugal system of the chick - Calaza,K.C. (2000)
In this study we characterize the presence of muscarinic acetylcholine receptors (mAChR) in the isthmo-optic nucleus (ION) of chicks by immunohistochemistry with the M35 antibody. Some M35-immunoreactive fibers were observed emerging from the retinal optic nerve insertion, suggesting that they could be centrifugal fibers. Indeed, intraocular injections of cholera toxin B (CTb), a retrograde tracer, and double-labeling with M35 and CTb in the ION confirmed this hypothesis. The presence of M35-immunoreactive cells and the possible mAChR expression in ION and ectopic neuron cells in the chick brain strongly suggest the existence of such a cholinergic system in this nucleus and that acetylcholine release from amacrine cells may mediate interactions between retinal cells and ION terminals.